2020
DOI: 10.7759/cureus.9941
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Outcomes of Breast Cancer Surgery in a Developing Country

Abstract: Background Breast cancer remains the most common cause of cancer related mortality amongst women in Pakistan. Postoperative complications can demoralize the patients and potentially delay adjuvant treatment, leading to adverse outcomes. The overarching aim of the study is to delineate the early postoperative outcomes of breast cancer surgery in Pakistan. Materials and Methods A retrospective study involving patients who underwent breast cancer surgery from June 2016 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…The rarest complications were represented by the wound infection: 2 cases (10.5%) and the axillary lymphocele: 1 case (5.3%). The results obtained were partially correlated with recent data from the literature indicating seroma as the most common postoperative complication followed by wound infection, hematoma and flap necrosis (16). Of note is the absence of seroma in patients who underwent surgery, which can be explained by the use of drainage tubes at the end of the surgery.…”
Section: Resultssupporting
confidence: 80%
“…The rarest complications were represented by the wound infection: 2 cases (10.5%) and the axillary lymphocele: 1 case (5.3%). The results obtained were partially correlated with recent data from the literature indicating seroma as the most common postoperative complication followed by wound infection, hematoma and flap necrosis (16). Of note is the absence of seroma in patients who underwent surgery, which can be explained by the use of drainage tubes at the end of the surgery.…”
Section: Resultssupporting
confidence: 80%
“…On the contrary, the rate of surgical site infections, 14.9% in our study, was higher in our patient population compared to published reports which ranged between 2 and 6% [24][25][26]. Reports indicated older age, Hypertension, high volume of drainage output, serum protein concentration, longer operative time, and lack of patient-controlled analgesia to be risk factors for seroma formation [23,[27][28][29]. In contrast, in our study, we found a higher seroma rate in patients with a history of diabetes, neoadjuvant chemotherapy, 10 or more lymph node dissection and a higher BMI (> 24 kg/m 2 ).…”
Section: Discussioncontrasting
confidence: 78%
“…Reports indicated older age, Hypertension, high volume of drainage output, serum protein concentration, longer operative time, and lack of patient-controlled analgesia to be risk factors for seroma formation [ 23 , 27 29 ]. In contrast, in our study, we found a higher seroma rate in patients with a history of diabetes, neoadjuvant chemotherapy, 10 or more lymph node dissection and a higher BMI (> 24 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 2015 Lancet Commission on Global Surgery, a number of studies on the feasibility and safety of surgical procedures for several cancers including orofacial, gastrointestinal, urological, gynecological, breast, brain, and spine tumors have been performed in countries including Egypt, India, Nigeria, Pakistan, and Taiwan. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] It is notable that most of these studies were performed at a single institution, with multicenter collaborative studies being rare. Surgical interventions described mostly include resections which aim to maximize overall survival and progression-free survival such as pancreaticoduodenectomy, gastrectomy, hepatectomy, cytoreductive surgery, laparoscopic colorectal surgery, radical cystectomy, partial nephrectomy, and brain and spine tumor removal.…”
Section: Local Innovations and Feasibility Studiesmentioning
confidence: 99%